Effect Of Old Meat Fish Bait Decay Pari (Trigon Sephen) To Catch Bubu Crab (Trap) In Village Depths Echo Nine River District City Province Dumai Riau - Nando, Riyan; Brown, Arthur; Rengi, Pareng (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in November 2014 in the village of Lubuk Gaung subdistrict nine river Dumai city of Riau province. The purpose of this study was to determine whether there is influence of bait meat spoilage old stingray (Trygon sephen) to catch crab pots (trap). The experimental method used is that test the effectiveness of the bait in crab traps fishing gear (trap) in the treatment of waters with long decay different. Based on the results of the study between the level of treatment of different types of bait, it is known that the use of bait fish trap crabs freshly caught stingray many as eight tails with a total weight of 2525 grams, use bait stingray decomposed for 1 day caught as many as 10 fish with a total weight of 2895 grams, use baits stingray decomposed for two days caught as many as 16 fish with a total weight of 5160 grams, and crab traps use bait stingray decomposed for 3 days caught as many as 3 heads with a total weight of 970 grams. Lack of interest crabs to feed the stingrays decomposed for 3 days allegedly due to the composition of the material contained in the feed stingrays meat can no longer stimulate the olfactory senses crabs so that the feed be less favored by crabs.Keywords: crab pots, meat stingray, long decay, bait